KAJIAN 5 (LIMA) TEPAT PROGRAM BANTUAN SISWA MISKIN TINGKAT SMA DI SMA NEGERI 9 SEMARANG - Satrio Kurniadi Widodo; Sri Suwitri; Hartuti Purnaweni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Poor student aid program policies which refers to the regulations of president number 15 of 2010 regarding the acceleration of poverty reduction. The purpose of the policy poor student aid program to help school-age children from poor families and household to be able to stay in school, not drop out of school and later in the future they can broke the chains of poverty that currently handcuff their family. That goal can be achieved through effective implementation, judging from the accuracy of the policy, accuracy of the implementation, accuracy of the target, accuracy of the environment and accuracy of the process. Process of the Implementation of program policy poor student aid in achieving the goals contained inhibiting factor and support factor. Based on the theory George C. Edwards III factor that support and hinder are Communication, Resources, Disposition and Bureaucratic Structure. Based on the existing barriers in the implementation of the program policy poor student aid of senior high school level in Semarang city, Author recommend as follows : (1) Make a report format which was related to student reports format recipients of aid poor students. (2) Propose he addition of personnel to be more adequate policy implementation. (3) Maximize the function of monitoring of management institutions and implementing program policies poor student aid at the local level, such as the provincial education office and the city education department of the executive apparatus at each educational unit.